Two Houses - Joseph N. Biondo (Oz, 2003)
We are living in a period increasingly enamored with high technology. The world keeps moving faster and faster. Therefore it is not unreasonable to believe that people regard their private domain as a safeguard against an inhospitable world of uncontrollable change.